Nonviolence to animals, earth, and self in Asian traditions - Chapple, Christopher Key, 1954- (SUNY series in religious studies., 1993)
This book probes the origins of the practice of nonviolence in early India and traces its path within the Jaina, Hindu, and Buddhist traditions. It speaks to a variety of contemporary issues, such as vegetarianism, animal and environmental protection, and the cultivation of religious tolerance.